A Hubris Theory of Entrepreneurship - Hayward, Mathew L. A.; Shepherd, Dean A.; Griffin, Dale (Management Science, 2006)
This paper develops a hubris theory of entrepreneurship to explain why so many new ventures are created in the shadow of high venture failure rates: More confident actors are moved to start ventures, and then act on such confidence when deciding how to allocate resources in their ventures. Building on theory and evidence from the behavioral decision-making literature, we describe how founders’ socially constructed confidence affects the manner in which they interpret information about their prior and current ventures. We then link founders’ propensity to be overconfident to their decisions to allocate, use, and attain resources. In our model, founders with greater socially constructed confidence tend to deprive their ventures of resources and resourcefulness and, therefore, increase the likelihood that their ventures will fail.